MODE OF ACTION OF LANTANA CAMARA EXTRACTS ON ENZYMES ASPARTATE AMINO TRANSFERASE AND ALANINE AMINO TRANSFERASE ACTIVITY IN TARGET AND NONTARGET ORGANISMS - S. RAJAN, DIVYA (The Bioscan, 2013)
The plant Lantana camara on the basis of study conducted found to show effective larvicidal activity. The present study deals with the mode of action of Lantana camara extract on enzymes, Aspartate Amino Transferase and Alanine Amino Transferase activity in target and non-target organisms. The major transaminase system of the body such as AsAT and AlAT were significantly inhibited by the plant extract. A significant decrease in the activity of above two enzyme systems were observed from the fourth h of incubation onwards. The transaminase system of mosquito larvae was more sensitive to Lantana camara extract than that of vertebrate system such as Anabas testudineus and Rana hexadactyla which are the non-target organisms seen in the aquatic habitat. The major transaminase systems of the body such as AsAT and AlAT were inhibited in a dose dependent manner under both invitro and invivo conditions. The change of pH from alkaline (normal larvae) to acidic (intoxicated larvae), may also be sufficient for inhibiting or blocking most of the enzymatic reactions leading to the death of the organisms. The results of this experiment indicated that the shrub Lantana camara could be studied further in detail and its benificial effects to the control of vector bron diseases could be utilised for healthy environments.